Soluções amistosas perante a comissão interamericana de direitos humanos: impactos transformadores da autocomposição - Serva, Clara Pacce Pinto (2022)
This study investigates if the Friendly Settlement Mechanism, provided as part of the conciliatory function of the Inter-American Commission on Human Rights, presents itself as a path for structural results in the Inter-American System of Human Rights. Therefore, it analyses the mandate and functions of the IACHR, examines the Friendly Settlement Mechanism and the guarantee of integral reparation in the Inter-American System. It provides for an outline of the contemporary access to justice, composed by a multidoor justice system with third parties’ solutions and consensual solutions, elaborating on the overview and the challenges of strategic litigations, and the dimensions of integral reparation. With such theoretical foundations, it analyzes all the Friendly Settlements Case Reports to verify the way different States use the mechanism, the actors of consensus (notably Civil Society Organizations), the multiple types of violations, the categories of reparation provided in the settlements and the extent of compliance, delineating a map of Friendly Settlements. As a conclusion, it aims at understanding the impacts of the mechanism, questioning if the consensual solution is a path for systematic changes and, thus, for the strategic litigation